Quality Initiative to Reduce Failed Trial of Labor after Cesarean Using Calculated VBAC Success Likelihood - Williams, Frank B.; Pierce, Hayley; McBride, Carole A.; DeAngelis, Justin; McLean, Kelley (American Journal of Perinatology, 2022)
Objective Vaginal birth after cesarean can reduce morbidity associated with multiple cesarean deliveries. Failed vaginal birth after cesarean is associated with increased maternal and neonatal morbidity. The Maternal-Fetal Medicine Units Vaginal Birth After Cesarean calculator is a validated tool to predict the likelihood of successful trial of labor after cesarean. Predicted likelihood < 60% has been associated with increased maternal and neonatal morbidity. We sought to determine if formal incorporation of calculated vaginal birth after cesarean likelihood into patient-centered counseling would reduce failed vaginal birth after cesarean.Study Design This is a quality improvement intervention at a single tertiary-care academic medical center, in which standardized patient counseling was implemented, facilitated by an electronic medical record template featuring patient-specific likelihood of vaginal birth after cesarean success. Term singleton pregnancies with history of one to two cesareans were included; those with contraindication to labor were excluded. Historical controls (January 2016–December 2018, n = 693) were compared with a postimplementation cohort (January 2019–April 2020, n = 328). Primary outcome was failed vaginal birth after cesarean.Results Fewer patients in the postintervention cohort had a history of an arrest disorder (PRE: 48%, 330/693 vs. POST: 40%, 130/326, p = 0.03); demographics were otherwise similar, including the proportion of patients with <60% likelihood of success (PRE: 39%, 267/693, vs. POST: 38%, 125/326). Following implementation, induction of labor in patients with a <60% likelihood of successful vaginal birth after cesarean decreased from 17% (45/267) to 5% (6/125, p < 0.01). The proportion of failed vaginal birth after cesarean decreased from 33% (107/329) to 22% (32/143, p = 0.04). Overall vaginal birth after cesarean rate did not change (PRE: 32%, 222/693, vs. POST: 34%, 111/326, p = 0.52).Conclusion An intervention targeting provider counseling that included a validated vaginal birth after cesarean success likelihood was associated with decreased risk of failed trial of labor after cesarean without affecting overall vaginal birth after cesarean rate.Key Points
Keywords: cesarean delivery; induction of labor; patient counseling; quality improvement; repeat cesarean; TOLAC; trial of labor; VBAC; vaginal birth after cesarean